The influence of Antarctic ice loss on polar motion: an assessment based on GRACE and multi-mission satellite altimetry - Göttl, Franziska; Groh, Andreas; Schmidt, Michael; Schröder, Ludwig; Seitz, Florian; Technische Universität München, Deutsches Geodätisches Forschungsinstitut, Munich, Germany; Technische Universität Dresden, Institut für Planetare Geodäsie, Dresden, Germany; Federal Agency for Cartography and Geodesy, Leipzig, Germany (Earth, Planets and Space, 2021)
Increasing ice loss of the Antarctic Ice Sheet (AIS) due to global climate change affects the orientation of the Earth’s spin axis with respect to an Earth-fixed reference system (polar motion). Here the contribution of the decreasing AIS to the excitation of polar motion is quantified from precise time variable gravity field observations of the Gravity Recovery and Climate Experiment (GRACE) and from measurements of the changing ice sheet elevation from altimeter satellites. While the GRACE gravity field models need to be reduced by noise and leakage effects from neighboring subsystems, the ice volume changes observed by satellite altimetry have to be converted into ice mass changes. In this study we investigate how much individual gravimetry and altimetry solutions differ from each other. We show that due to combination of individual solutions systematic and random errors of the data processing can be reduced and the robustness of the geodetic derived AIS polar motion excitations can be increased. We investigate the interannual variability of the Antarctic polar motion excitation functions by means of piecewise linear trends. We find that the long-term behavior of the three ice sheet subregions: EAIS (East Antarctic Ice Sheet), WAIS (West Antarctic Ice Sheet) and APIS (Antarctic Peninsula Ice Sheet) is quite different. While APIS polar motion excitations show no significant interannual variations during the study period 2003-2015, the trend of the WAIS and EAIS polar motion excitations increased in 2006 and again in 2009 while it started slightly to decline in 2013. AIS mass changes explain about 45% of the observed magnitude of the polar motion vector (excluding glacial isosatic adjustment). They cause the pole position vector to drift along 59 ◦ East longitude with an amplitude of 2.7 mas/yr. Thus the contribution of the AIS has to be considered to close the budget of the geophysical excitation functions of polar motion. Deutsche Forschungsgemeinschaft http://dx.doi.org/10.13039/501100001659 European ...